ASSA13-02-2 Inducibility of Atrial Arrhythmia After Circumferential Pulmonary Vein Isolation in Patients with Paroxysmal Atrial Fibrillation: Clinical Predictor and Outcome During Follow-Up. (29th April 2013) - Hong, Zhang; Zu-Lu, Wang; Yan-Chun, Liang; Ming, Liang; Ya-Ling, Han; Zhi-Qing, Jin; Shi-Bei, Li; Shu-Yin, Shi
Abstract : Background: Inducibility of atrial arrhythmia after circumferential pulmonary vein isolation (CPVI) in patients with paroxysmal atrial fibrillation (AF) were analysed to assess whether inducibility of atrial arrhythmia could be used as a clinical predictor of AF recurrence and whether non-inducibility of AF was a clinically useful end point. Methods: Forty one consecutive patients with symptomatic paroxysmal AF underwent CPVI guided by 3D mapping system and single Lasso technique. After achievement of CPVI, the induction of atrial arrhythmia (AA) was performed. AA was induced by rapid atrial pacing within the proximal coronary sinus and right atrium. AA was considered inducible only if its duration was more than 30 seconds. Symptoms, Surface ECG, and 24h Holter recording were followed up after the procedure. Results: Sustained atrial arrhythmias were induced after CPVI in 16 of 41 patients (39.0%). Thirteen of the 35 patients (37.1%) had inducible AA after the initial procedure and 3 of the 6 patients (50%) after the second procedure, and there was no difference between the two groups ( P > 0.05). There were no differences in the baseline data between the two groups ( P > 0.05). During an average 6 months of follow-up, 7 of the 16 patients (43.8%) in the AF inducible group had AF recurrence, and 8 of the 25 patients (32.0%) in the AF non-inducible group had AF recurrence ( P > 0.05). After the second procedure, 1 of the 3 patients in the AF inducible group had AF recurrence, and no patient of the 3 patients in the AF non-inducible group had AF recurrence ( P > 0.05). Four of the 9 patients (44.4%) whose inducible AA lasted between 1 min and 5 min had AF recurrence; 1 of the 3 patients (33.3%) whose AA duration more than 5 min and less than 10 min had AF recurrence; 2 of the 4 patients (50%) whose AA duration more than 10 min had AF recurrence. The recurrences among the above groups showed no significant difference ( P > 0.05). The sensitivity, speciﬁcity, positive, and negative predictive values of the AF induction test to predict the 6-month ablation outcome were 41.7%, 65.2%, 27.2% and 68.2%, respectively. Conclusions: Inducibility of atrial arrhythmia could not predict the clinical efficacy of CPVI in patients with paroxysmal AF, and non-inducibility could not be qualified as a reliable procedural endpoint.